Trabalhadores e viveres sociais: transformações e permanência na agricultura e no município de Santa Juliana MG (1990-2010) - Morais, Marco Túlio Melo (2012)
This paper discusses the process of transformation in the relations of labor and production that occurred in Santa Juliana mainly from the year 1997, whereas this process, it seems, is directly linked to the need of manpower for the job crops in the area. We seek to understand how these changes were processed addressing the interests involved by both workers and managers on the part of the municipality and the landowners. From the trajectory of different workers seek to understand the dynamics of labor exploitation in the field justified, or rather guided by the notion of protecting and improving the environment. Therefore, to understand how the transformation proceed in the social, economic and cultural city as well as understanding the meanings attributed to this new dynamic in the constitution of local residents by both older and younger, and by workers coming from other regions of the country are issues in this investigation.